Structural Studies of Fibrinolysis by Electron and Light Microscopy - Weisel, John W.; Veklich, Yuri; Collet, Jean-Philippe; Francis, Charles W. (Thrombosis and Haemostasis, 1999)
Much is known about the fibrinolytic system that converts fibrin-bound plasminogen to the active protease, plasmin, using plasminogen activators, such as tissue-type plasminogen activator (t-PA) and urokinase-type plasminogen activator. Plasmin then cleaves fibrin at specific sites and generates soluble fragments, many of which have been characterized, providing the basis for a molecular model of the polypeptide chain degradation.1-3 Soluble degradation products of fibrin have also been characterized by transmission electron microscopy, yielding a model for their structure.4 Moreover, high resolution, three-dimensional structures of certain fibrinogen fragments has provided a wealth of information that may be useful in understanding how various proteins bind to fibrin and the overall process of fibrinolysis (Doolittle, this volume).5,6Both the rate of fibrinolysis and the structures of soluble derivatives are determined in part by the fibrin network structure itself. Furthermore, the activation of plasminogen by t-PA is accelerated by the conversion of fibrinogen to fibrin, and this reaction is also affected by the structure of the fibrin. For example, clots made of thin fibers have a decreased rate of conversion of plasminogen to plasmin by t-PA, and they generally are lysed more slowly than clots composed of thick fibers.7-9 Under other conditions, however, clots made of thin fibers may be lysed more rapidly.10 In addition, fibrin clots composed of abnormally thin fibers formed from certain dysfibrinogens display decreased plasminogen binding and a lower rate of fibrinolysis.11-13 Therefore, our increasing knowledge of various dysfibrinogenemias will aid our understanding of mechanisms of fibrinolysis (Matsuda, this volume).14,15To account for these diverse observations and more fully understand the molecular basis of fibrinolysis, more knowledge of the physical changes in the fibrin matrix that precede solubilization is required. In this report, we summarize recent experiments utilizing transmission and scanning electron microscopy and confocal light microscopy to provide information about the structural changes occurring in polymerized fibrin during fibrinolysis. Many of the results of these experiments were unexpected and suggest some aspects of potential molecular mechanisms of fibrinolysis, which will also be described here.